Land Markets : Promoting the Private Sector by Improving Access to Land - Muir, Russell; Shen, Xiaofang (World Bank, Washington, DC, 2012)
Land markets that allow access to land-and to buildings-through secure property rights, at transparent prices, and with efficient permitting processes and land tax systems are essential to a good business environment. Creating such markets, however, can be a long, complex, politically charged process, especially where most land is untitled and where there are conflicting claims. But experience points to practical interim or step solutions that can have a positive impact and generate the political capital to reform the overall land market system.